KONSEP DASAR SUPERVISI PENDIDIKAN ISLAM - Rima Dewi Setiani I; Ahmad Manshur (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Islamic educational supervision plays a strategic role in improving the quality and professionalism of educators while integrating Islamic values into the learning process. Etymologically, the term supervision derives from the words super and vision, meaning “to see from above” or “to oversee.” In the context of Islamic education, supervision is understood as a form of service, guidance, and nurturing conducted in a humanistic and Islamic manner to assist teachers in developing competence, character, and effectiveness in teaching and learning. Supervision is not merely focused on administrative control but also emphasizes spiritual and moral aspects through the principle of amar ma’ruf nahi munkar (enjoining good and forbidding evil). The urgency of Islamic educational supervision lies in its function as a means of teacher development, enabling educators to adapt to modern challenges without losing their Islamic spirit. Through well-directed supervision, teachers receive guidance, motivation, and feedback to enhance professionalism and teaching quality. Furthermore, supervision serves to maintain the quality of educational institutions so that they remain grounded in the principles of aqidah, sharia, and noble character. Therefore, Islamic educational supervision holds a comprehensive meaning—not only as a control mechanism but also as a medium for nurturing and transforming Islamic values within the education system.